2020
DOI: 10.1016/j.psychsport.2020.101671
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to promote growth following adversity

Abstract: Background: Athletes experience adversity across many aspects of their lives. Challenging the dominant idea that adversity is just a negative experience, a significant body of research in sport has demonstrated that these adverse events can also act as catalysts for positive change (Howells, Fletcher, & Sarkar, 2017). Yet, a limited number of researchers have focused on how to promote growth following adversity in sport. To support this line of inquiry our aim in this study was to facilitate knowledge trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…Por ejemplo, en el presente estudio hay una mayor activación de las conexiones de los dominios de cambio espiritual-existencial, apreciación por la vida y relaciones interpersonales que promueven el mantenimiento sistemático del CPT, conformados por variables que son probabilísticamente dependientes en mayor grado que los otros elementos de la red. Por tanto, estos dominios son de mayor interés para intervenir a aquellas personas que han sufrido traumas relacionados a la muerte de un ser querido que favorezcan su crecimiento y su proceso de duelo (Howells et al, 2020) desde el modelo psicoterapéutico integrado del CPT que incluyen características narrativas, interpersonales y existenciales (Tedeschi y Moore, 2021).…”
Section: Discussionunclassified
“…Por ejemplo, en el presente estudio hay una mayor activación de las conexiones de los dominios de cambio espiritual-existencial, apreciación por la vida y relaciones interpersonales que promueven el mantenimiento sistemático del CPT, conformados por variables que son probabilísticamente dependientes en mayor grado que los otros elementos de la red. Por tanto, estos dominios son de mayor interés para intervenir a aquellas personas que han sufrido traumas relacionados a la muerte de un ser querido que favorezcan su crecimiento y su proceso de duelo (Howells et al, 2020) desde el modelo psicoterapéutico integrado del CPT que incluyen características narrativas, interpersonales y existenciales (Tedeschi y Moore, 2021).…”
Section: Discussionunclassified
“…Moreover, the intervention studies aimed at promoting growth in the wider growth literature have shown mixed efficacy (cf. Howells et al, 2020). In helping contribute to research addressing the genuine unknowns of how to promote growth following negative experiences, as noted by Howells and colleagues, this paper offers suggestions of which psychological mechanisms are important to enhance, build, and develop within athletes.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 96%
“…In the sport psychology literature, it is established that sport-related adversity can catalyze athlete growth and facilitate elite performance (Galli & Reel, 2012;Howells et al, 2020;McCormick et al, 2018;Roy-Davis et al, 2017;Sarkar et al, 2015;Tamminen et al, 2013;Wadey et al, 2013). For example, Connaughton and colleagues (2010), and Galli and Reel (2012), examined the impact of sport-related adversity on athletic performance for both men and women elite athletes.…”
Section: Sport-related Adversity and Growthmentioning
confidence: 99%
“…According to Stebbins (2007), "serious leisure" consists of the "…systematic pursuit of an amateur, a hobbyist, or a volunteer activity sufficiently substantial and interesting for the participant to find a career there in the acquisition and expression of a combination of its special skills, knowledge, and experience" (p. 5). Using recent feminist theory on popular and neoliberal feminism (Banet-Weiser, 2015;Banet-Weiser, et al, 2020;Rottenburg, 2014) to frame our discussion and analysis, our study combines feminist leisure studies (e.g., Dilley & Scraton, 2010;Lamont et al, 2019;Lloyd & Little, 2010;Shaw, 1994;Wearing, 1998) and sport psychology (e.g., Galli & Reel, 2012;Howells et al, 2020;McCormick et al, 2018;Roy-Davis et al, 2017;Sarkar et al, 2015;Tamminen et al, 2013;Wadey et al, 2013) to examine the experiences of seven women Ironman athletes.…”
mentioning
confidence: 99%